INTENTION TO USE DIGITAL BANK: ROLE OF PERCEIVED EASE OF USE, CUSTOMER KNOWLEDGE, SERVICE QUALITY, AND SYSTEM SECURITY - Andrianto Prasetya Nugroho; Etty Zuliawati Zed; Fitri Syakila (Jurnal Ekonomi, 2023)
The purpose of this study is to evaluate the factors affecting the intention to use digital banking on Jenius application users. Empirical studies were conducted to determine the effect of perceived ease of use, customer knowledge, service quality, and system security on the intention to use Jenius digital bank. Data were collected from 100 users of Jenius digital bank. The analysis result show that: (1) perceived ease of use has no effect on the intention to use the service; (2) customer knowledge has no effect on the intention to use the service; (3) service quality has a positive effect on the intention to use toward the service; (4) system security has a positive impact on intention to use toward the service. Service quality and system security are essential for further attention, considering that digital banks carry out almost all of their operations digitally without physical branches. Perceived ease of use, customer knowledge, service quality, and system security are able to explain intention to use Jenius digital bank by 80,2%.